(untitled) (Acta Scientiarum. Health Sciences, 2012)
This study identified at the moment of psychiatric hospitalization in a general hospital the meaning and implications of schizophrenia from the perspective of people who experience it. Interviews were conducted with ten patients with schizophrenia, diagnosed with the disorder for at least five years, hospitalized in the psychiatric ward of Clinical Hospital of Marília, based on the following question: what is the meaning and implications of living with schizophrenia? The interviews were taped, transcribed and subjected to thematic analysis. It was identified the category ‘Discovering the schizophrenia’ and three themes: Feelings experienced in the discovery and acceptance process; Knowledge about the disorder, diagnosis and treatment; Expectations for the future from the discovery of the disease. The results led to a greater understanding of the perception that patients with schizophrenia have about the disease and treatment, the implications for the future, as well as the difficulties and the suffering experienced in the discovery, identified during the acceptance process. This discovery can contribute to understanding these issues by professionals and to improve the implementation of nursing care.